The multidimensional role of calcium in atrial fibrillation pathophysiology: mechanistic insights and therapeutic opportunities - Nattel, Stanley; Dobrev, Dobromir (European heart journal, 2012)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, and its prevalence is increasing with the ageing of the population. Presently available treatment options are far from optimal and new insights into underlying mechanisms are needed to improve therapy. A variety of recent lines of research are converging to reveal important and relatively underappreciated multidimensional roles of cellular Ca2+ content, distribution, and handling in AF pathophysiology. The objective of the present paper is to review the participation of changes in cell Ca2+ and related processes in the mechanisms that lead to AF initiation and maintenance, and to consider the relevance of new knowledge in this area to therapeutic innovation.